2007
DOI: 10.1369/jhc.7a7176.2007
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization and Cell Expression of Lung Resistance-related Protein (LRP) in Normal and Tumoral Human Respiratory Cells

Abstract: Lung resistance-related protein (LRP) is an integral part of the multidrug resistance (MDR) phenotype involved in cell resistance toward xenobiotics or chemotherapy. The aim of this study was to compare the intracellular localization and cell expression of LRP in normal bronchial cells and their tumoral counterparts from non-small cell lung cancer (NSCLC). LRP expression was also investigated concurrently with DNA ploidy and chromosome 16 ( lrp gene locus) aberrations. Confocal microscopy showed that LRP local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…Additionally, it must be mentioned that several proteins encoded by very important (proto)oncogenes (EGF/EGFR, Src, cJun), but also tumor-suppressor genes (e.g. PTEN, [35,36,136] or maintain the high MVP expression already present in the respective normal tissues [117,118,157]. Accordingly, in some tumor types MVP levels correlated with a worse prognosis not related to chemotherapy failure [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it must be mentioned that several proteins encoded by very important (proto)oncogenes (EGF/EGFR, Src, cJun), but also tumor-suppressor genes (e.g. PTEN, [35,36,136] or maintain the high MVP expression already present in the respective normal tissues [117,118,157]. Accordingly, in some tumor types MVP levels correlated with a worse prognosis not related to chemotherapy failure [37].…”
Section: Discussionmentioning
confidence: 99%
“…Vaults are frequently expressed in tissues chronically exposed to the environment and consequently prone to get in contact with xenobiotics, including the epithelia of lung and digestive tract as well as early stages of embryonic development [62,117,118]. In addition to the distinct correlation of intrinsic drug resistance with MVP expression in several human malignancies in vitro and in vivo [16,34], MVP is almost generally overexpressed in drug resistant human cancer cells selected against a wide array of chemotherapeutic drugs [29,33,55,119].…”
Section: Vaults and Drug Resistance: An Intricate Liaisonmentioning
confidence: 99%
“…These results suggest that the regulatory mechanism of both LRP and MRP1 expression is associated with the multidrug resistance phenotype. 28 The results of some studies point to the fact that one of the important mechanisms of tumorigenesis and resistance to anticancer drugs is blockade of the pathway triggering apoptosis. 38,39 Understanding of the molecular mechanisms of resistance to DDP may lead to improved treatment strategies for DDP-resistant tumors and increased survival in patients with lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The functional role of overexpression of vaults is still speculative, but it has been proposed to play an important role in drug resistance. Vaults are frequently expressed in tissues chronically exposed to the environment and consequently prone to get in contact with xenobiotics, including the epithelia of lung and digestive tract as well as early stages of embryonic development [3,16,17]. Previous studies showed that MVP is almost generally overexpressed in drug-resistant human cancer cells selected against a wide array of chemotherapeutic drugs [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%